Towards bioengineered skeletal muscle: recent developments in vitro and in vivo. Issue 3 (10th August 2021) - Quigley, Anita; Ngan, Catherine; Firipis, Kate; O'Connell, Cathal D.; Pirogova, Elena; Moulton, Simon E.; Williams, Richard J.; Kapsa, Robert M.I.
Abstract: Skeletal muscle is a functional tissue that accounts for approximately 40% of the human body mass. It has remarkable regenerative potential, however, trauma and volumetric muscle loss, progressive disease and aging can lead to significant muscle loss that the body cannot recover from. Clinical approaches to address this range from free-flap transfer for traumatic events involving volumetric muscle loss, to myoblast transplantation and gene therapy to replace muscle loss due to sarcopenia and hereditary neuromuscular disorders, however, these interventions are often inadequate. The adoption of engineering paradigms, in particular materials engineering and materials/tissue interfacing in biology and medicine, has given rise to the rapidly growing, multidisciplinary field of bioengineering. These methods have facilitated the development of new biomaterials that sustain cell growth and differentiation based on bionic biomimicry in naturally occurring and synthetic hydrogels and polymers, as well as additive fabrication methods to generate scaffolds that go some way to replicate the structural features of skeletal muscle. Recent advances in biofabrication techniques have resulted in significant improvements to some of these techniques and have also offered promising alternatives for the engineering of living muscle constructs ex vivo to address the loss of significant areas of muscle. This review highlights current research in this area and discusses the next steps required towards making muscle biofabrication a clinical reality.